"Armor‐Plating" Enzymes with Metal–Organic Frameworks (MOFs). Issue 23 (25th March 2020) - Huang, Siming; Kou, Xiaoxue; Shen, Jun; Chen, Guosheng; Ouyang, Gangfeng
Abstract: Cell‐free enzymatic catalysis (CFEC) is an emerging biotechnology that enable the biological transformations in complex natural networks to be imitated. This biomimetic approach allows industrial products such as biofuels and biochemical to be manufactured in a green manner. Nevertheless, the main challenge in CFEC is the poor stability, which restricts the effectiveness and lifetime of enzymes in sophisticated applications. Immobilization of the enzymes within solid carriers is considered an efficient strategy for addressing these obstacles. Specifically, putting an "armor‐like" porous metal–organic framework (MOF) exoskeleton tightly around the enzymes not only shields the enzymes against external stimulus, but also allows the selective transport of guests through the accessible porous network. Herein we present the concept of this biotechnology of MOF‐entrapped enzymes and its cutting‐edge applications. Abstract : Armorous advances : Embedding enzymes within metal–organic framework (MOF) exoskeletons improves the stability and life‐time of enzymes. This Minireview shows the progress made with MOFs‐embedded enzymes. It focuses on new embedding strategies for constructing enzyme@MOF biocomposites and the factors that influence the change in enzymatic activity. In addition, applications of enzyme@MOFs in fields such as biocatalysis, sensing, and nanocatalysis therapeutics, are presented.